Arterial hypertension and coronary heart disease: the place of angiotensin II receptor antagonists - E. O. Taratukhin (Кардиоваскулярная терапия и профилактика)
The paper considers arterial hypertension and coronary heart disease as pathologies which share multiple pathogenetic mechanisms. The role of angiotensin II receptor antagonists (ARA) in the effective treatment of these diseases and in prevention of their complications is discussed. The modern views on ARA and their indications are presented.